Faktor Penyebab Keterlambatan Siswa dalam Melanjutkan Pendidikan Tinggi di Kota Sorong - Agustin, Talita Tri; Widodo, Agus; Andyastuti, Etty; Hidayat, Rahmat; Pristiani, Yunita Dwi; Hajuan, Muhammad Akbar (Efektor, 2024)
This research aims to understand the factors causing students to experience delays in pursuing higher education in Sorong. The research method is a descriptive qualitative approach, collecting data through observation, interviews, questionnaires, data analysis, and documentation. In the Klabim Sub-District of Sorong City, the community's understanding of the importance of education is still limited. However, some hope their children can continue their education to a higher level, despite some obstacles. The results of this study reveal several factors influencing students' delays in pursuing higher education, both internal and external factors. Internal factors include a lack of motivation and interest among students, as well as their tendency to choose work over continuing to college. Meanwhile, external factors include economic issues, lack of social support, increasing rates of early marriage, and traditional marriage practices without official registration. The government has attempted to address these issues through scholarship programs for Papuan students, but implementation has not yet been optimal in achieving the desired targets.